Diagnostic performance of thermograms and mammograms for breast cancer detection - Amaral, Elizabete Marques (2014)
In this paper we carry out a comparative study between mammograms and thermograms, involving 200 women, in order to bring a new light on the current situation of thermography as an effective tool to support mammography in prevention and monitoring the breast cancer.